2016
DOI: 10.18632/oncotarget.10343
|View full text |Cite
|
Sign up to set email alerts
|

Lin28B promotes Müller glial cell de-differentiation and proliferation in the regenerative rat retinas

Abstract: Retinal regeneration and repair are severely impeded in higher mammalian animals. Although Müller cells can be activated and show some characteristics of progenitor cells when injured or under pathological conditions, they quickly form gliosis scars. Unfortunately, the basic mechanisms that impede retinal regeneration remain unknown. We studied retinas from Royal College of Surgeon (RCS) rats and found that let-7 family molecules, let-7e and let-7i, were significantly overexpressed in Müller cells of degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
(51 reference statements)
2
7
0
Order By: Relevance
“…Western blot analysis was performed according to our previous methods [ 43 ]. After eyes were enucleated from sacrificed mice, the retinas were isolated from the globe and mixed in ice-cold tissue lysis buffer (1% PSMF + 99% RIPA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis was performed according to our previous methods [ 43 ]. After eyes were enucleated from sacrificed mice, the retinas were isolated from the globe and mixed in ice-cold tissue lysis buffer (1% PSMF + 99% RIPA).…”
Section: Methodsmentioning
confidence: 99%
“…Visual electrophysiological tests were performed as described previously [ 41 , 43 ]. Before the test, mice at P14 were dark-adapted for nearly 12 h. Intramuscular injections of amine (100 mg/kg) and xylazine (12 mg/kg) were performed for anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…These events cause an increase in mature microRNA levels in neurons and result in cellular repair [ 15 17 ]. The work by Tao and his colleagues suggested that the Lin28-let-7-Dicer pathway plays a critical role in retinal neurogenesis and regeneration [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, proliferation of murine MGCs can be stimulated by overexpression of Ascl1, a transcription factor essential during retinal development ( Pollak et al, 2013 ). Pharmacological perturbation of specific signaling pathways can also stimulate the neural regenerative potential of mammalian MGCs; these include, for instance, Wnt/β-catenin, EGF, FGF, and insulin pathways ( Karl et al, 2008 ; Osakada et al, 2007 ; Close et al, 2006 ; Todd et al, 2015 ; Ooto et al, 2004 ; Tao et al, 2016 ; Yao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%